Comparison of Carvedilol and Propranolol in the Treatment of Portal Hypertension in Cirrhosis - KASHIF MAHMOOD MALIK M. NABEEL AKBAR, TALAT NAHEED (Journal of Fatima Jinnah Medical University, 2018)
Cirrhosis of liver is a major international and national health hazard that causes very significant morbidity and mortality in our country. In Pakistan, the commonest cause of liver cirrhosis is chronic viral hepatitis. Portal hypertension is one of the major complications of liver cirrhosis.4 Carvedilol is a nonselective blocker with 1-adrenergic blocking activity. It has been shown to decrease portal pressure in cirrhotic patients. Additionally, carvedilol has a greater portal hypotensive effect than propranolol alone in patients with cirrhosis.9 Objective: To compare the efficacy of carvedilol and propranolol for the treatment of portal hypertension in patients of liver cirrhosis. Study Design and Place of Study: It was a randomized clinical trial. This study was conducted in the Department of Medical Unit-II, Sir Ganga Ram Hospital, Lahore. It was six months study from 26th March to 26th September 2010. Materials and Methods: One hundred patients of liver cirrhosis with portal hypertension were selected for this study. The patients were randomly divided into group A and B by using lottery method. Group A patients were given propranolol 40mg and group B patients were given carvedilol 25mg. Portal flow velocity was measured before and 90 minutes after the administration of the above mentioned drugs by a radiologist on Doppler ultrasonography and more than 20% decrease was considered as efficacy. Results: The mean age of the patients in group A was 51.6±11.3 years and in group B was 54.6±9.4 years. In group A, there were 37 (74%) male and 13 (26%) female patients and in group B, there were 27 (54%) male and 23 (46%) female patients. In group A, there were 12 (24%) patients had efficacy of treatment and in group B, there were 26 (52%) patients had efficacy of treatment. Conclusion: It is concluded from this study that carvedilol is more effective than propranolol for the treatment of portal hypertension in patients of liver cirrhosis. As in our study carvedilol is effective in 52% patients and propranolol in 24% patients.